Boatman [videorecording] - Aguiluz, Tikoy (s.n.], 1984)
An erstwhile boatman wanrs to do a little more than paddle his own canoe in the town famed for its waterfalls. He leaves the village of his roots for the city and lands a job as live sex actor called toro in street lingo derived from the Spanish term for bull. Quick success in his newfond profession delude him into regarding that the measure of a man is in his trousers. He has a partner on stage and off. Despite her cynisism and tough veneer, she sees in him a way out of the slums and the red light district.